Bone health of patients with juvenile idiopathic arthritis: a comparison between dual-energy X-ray absorptiometry and digital X-ray radiogrammetry. Issue 10 (October 2015) - Nusman, Charlotte M.; Anink, Janneke; Otten, Marieke H.; van Rossum, Marion A.J.; van Rijn, Rick R.; Maas, Mario; van Suijlekom-Smit, Lisette W.A.
Highlights: Juvenile idiopathic arthritis affects bone mineral density DXR determines bone mineral density on a hand radiograph. DXA (most used technique) and DXR correlate well on absolute scores. DXA and DXR do not correlate on Z-scores. DXR needs more validation before implementation in clinical practice. Abstract: Objectives: Juvenile idiopathic arthritis (JIA) affects bone mineral density (BMD). Dual-energy X-ray absorptiometry (DXA) is the most widely used technique to determine BMD. Digital X-ray radiogrammetry (DXR) is a feasible method for determination of cortical BMD on hand radiographs. This study aimed to compare DXR and DXA in the assessment of BMD in JIA patients. Methods: Thirty-five JIA patients with available DXA and hand radiograph within the same time period were included from the Dutch Arthritis and Biologicals in Children register. Outcome measures for BMD were Bone Health Index from DXR and BMD total body, BMD lumbar spine and Bone Mineral Apparent Density from DXA. All measures were transformed to Z-scores. Correlations were assessed with Pearson correlation coefficients. Results: Median age of the patients (60% female) was 11.7 years. Pearson correlation coefficient was significant for the absolute scores: 0.568–0.770 ( p  < 0.001). No significant correlation was found between the Z-scores of DXA and DXR. Conclusions: The BMD assessment from the DXR was correlated to DXA measures in a cohort of JIA patients, although only in absolute scores. Future steps for implementation of DXR in clinical practice include evaluation of responsiveness to change, predictive value and comparison with other imaging techniques.